Renal failure in cancer patients: results from the national cancer registry of Abidjan, Côte d'Ivoire - Kouamé Hubert Yao; Moctar Touré; Noel Coulibaly; Sery Patrick Diopoh; Serge Didier Konan; Yvon Kouassi; Innocent Adoubi (Society of Diabetic Nephropathy Prevention, 2017)
Background: Renal failure (RF) is a risk factor for morbidity and mortality in cancer patients. Objectives: To describe the profile of cancer patients with RF. Patients and Methods: This is a retrospective descriptive study of RF in patients enrolled in the national cancer registry of Abidjan, during the period from January 2012 to December 2015. The diagnosis of RF was confirmed based on a measured glomerular filtration rate (GFR) < 60 mL/min obtained using the Modification in Diet of Renal Disease (MDRD) formula. A comparison of patients with (n = 131) or without (n = 136) RF, followed by a logistic regression analysis, made it possible to identify the risk factors for RF. Results: The mean age was 54 ± 13.9 years in the group with RF versus 49 ± 14.8 years in the group without RF (P = 0.003). The etiologies of RF were urinary tract obstruction (41.2%), administration of platinum salts (19.8%) and water losses (12.2%). In multivariate analysis, age (P = 0.009), presence of hypertension (P = 0.02), uterine cancer (P = 0.0001) and prostate cancer (P = 0.014) were associated with the risk of RF in cancer patients. Factors such as male gender (P = 0.007), HIV infection (P = 0.021), GFR<15 mL/min (P = 0.002), and hemoglobin level <8 g/dL (P = 0.041) were associated with mortality in cancer patients with RF. Conclusions: Late diagnosis leads to renal complications with an increased risk of mortality.